PENGARUH PENGGUNAAN GADGET TERHADAP POLA PIKIR SISWA KELAS VIII SMP NEGERI 2 ULAWENG KECAMATAN ULAWENG KABUPATEN BONE - Abdullah, Achmad Dahlan (Jurnal Ilmiah Mandala Education (JIME), 2021)
This research is a quantitative descriptive study that aims to determine the effect of using gadgets on the mindset of class VIII students of SMP Negeri 2 Ulaweng, Ulaweng District, Bone Regency. The population in this study were all class VIII students of SMP Negeri 2 Ulaweng, Ulaweng District, Bone Regency and the sample was all students of class VIIIA SMP Negeri 2 Ulaweng, Ulaweng District, Bone Regency with a total of 30 students consisting of 17 male students and 13 female students. Data collection techniques were carried out using three methods, namely, questionnaires (questionnaires), documentation and interviews. Based on the data analysis, it was obtained an overview of the effect of using gadgets on students' mindsets, the percentage of several items including questionnaire item number 2 from 30 students, 8 people who answered "always" with a percentage of 26.67% and 12 students who said "sometimes". sometimes" with a percentage of 40.00%, questionnaire item number 3 of 30 students 24 of them answered "never" with a percentage of 80.00%, questionnaire item number 5 of 30 students 3 people answered "Yes" with a percentage of 10, 00%, 9 people answered "sometimes" with a percentage of 30.00%, and 15 students answered "never" with a percentage of 50.00%, questionnaire item number 8 of 30 students 19 people answered "no" with a percentage of 63 ,34 % of the questionnaire item number 10 of 30 students 19 people answered "Yes" with a percentage of 63.34% and 7 people who answered the category "sometimes" with a percentage of 23.33%. Thus it can be concluded that, the effect of using gadgets on students' mindsets can be said that the average of student answers per questionnaire item given explains that students tend to always use gadgets and consider gadgets themselves as a necessity, but on the other hand students also consider that the use of gadgets is a necessity. These gadgets can be one of the motivations for student learning and can divide the time between the use of gadgets.